4th European Conference of the International Federation for Medical and Biological Engineering ECIFMBE 2008 2327 November 2008 Antwerp, Belgium - Sloten, Jos.; Verdonck, Pascal.; Nyssen, Marc.; Haueisen, Jens. (IFMBE Proceedings, 2009)
The 4th European Congress of the International Federation for Medical and Biological Federation was held in Antwerp, November 2008. The scientific discussion on the conference and in this conference proceedings include the following issues: Signal & Image Processing ICT Clinical Engineering and Applications Biomechanics and Fluid Biomechanics Biomaterials and Tissue Repair Innovations and Nanotechnology Modeling and Simulation Education and Professional